Blue christmas - Andrews, Mary Kay, 1954- (New York : Harpercollins, 2007)
Bestselling author Andrews brings back the lovable characters from "Savannah Blues" and "Savannah Breeze" for a new funny and touching story that offers a little Christmas cheer with delicious Southern recipes throughout
"Now with more holiday cheer (new recipes too!)"--Cover
Keywords: Christmas stories; Savannah (Ga.) -- Fiction